New Trends in Uzbek Historical Fiction Cinema in Recent Years - Bakhtiyor Yakubov (Researchparks Publishing, 2021)
This article focuses on the development of historical films, which occupy a special place in Uzbek cinematography, and on new artistic and cultural principles. The restored process of historical filmmaking, stalled in the second decade of independence, new features and films related to it have been examined analytically.